2001
DOI: 10.1054/bjoc.2001.1807
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of intestinal tumorigenesis by nabumetone: induction of apoptosis and Bcl-2 downregulation

Abstract: Summary Treatment of MIN mice with the nonsteroidal anti-inflammatory drug, nabumetone, resulted in a dose-dependent suppression of intestinal tumorigenesis. In both the uninvolved MIN mouse colonic epithelium and HT-29 colon cancer cells, nabumetone downregulated the anti-apoptotic protein, Bcl-2, with concomitant induction of apoptosis, suggesting a potential mechanism for colon cancer chemoprevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Moreover, E-cadherin up-regulation is a common means of sequestration of the h-catenin to the plasma membrane (thus preventing nuclear translocation of h-catenin) and, hence, transcriptional activity. Indeed, our group has shown that E-cadherin induction occurs in response to a wide variety of chemopreventive agents, including the nonsteroidal anti-inflammatory drug nabumetone, ursodeoxycholic acid, and the vitamin D analogue (18,21) with a concomitant decrease in h-catenin signaling (21). In this regard, our data with PEG is consistent with these other known chemopreventive agents.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, E-cadherin up-regulation is a common means of sequestration of the h-catenin to the plasma membrane (thus preventing nuclear translocation of h-catenin) and, hence, transcriptional activity. Indeed, our group has shown that E-cadherin induction occurs in response to a wide variety of chemopreventive agents, including the nonsteroidal anti-inflammatory drug nabumetone, ursodeoxycholic acid, and the vitamin D analogue (18,21) with a concomitant decrease in h-catenin signaling (21). In this regard, our data with PEG is consistent with these other known chemopreventive agents.…”
Section: Discussionsupporting
confidence: 86%
“…The increased h-catenin protein levels enables nuclear translocation and transactivation of the lymphoid enhancer factor 1/Tcf-1, leading to transcriptional induction of a number of genes that are important in the early stages of colon carcinogenesis. Our group has previously shown that a number of structurally unrelated chemopreventive agents abrogated the increased h-catenin signaling through up-regulation of a plasma membrane protein E-cadherin (18,21). E-cadherin can avidly bind h-catenin, thereby suppressing the transcriptional activity of h-catenin by sequestering it away from the nucleus (22 -24).…”
Section: Introductionmentioning
confidence: 99%
“…The light scattering fingerprints obtained from the distal small bowels of MIN and control mice revealed dramatic qualitative differences as indicated by changes in backscatter intensity (different colors) in the small intestine but not the colon. This finding accurately reflects the future occurrence of neoplasia in this model in that >90% of adenomas are located in the small bowel with minimal tumorigenesis in the colon (17,18). Indeed, these data suggest that light scattering abnormalities predict a genetic substrate to neoplastic transformation before occurrence of neoplasia.…”
Section: Resultssupporting
confidence: 64%
“…The top candidates for colon cancer generated using the proteomic signature pipeline (left, red text) included alpremilast and mebendazole ( Nygren et al, 2013 ; Nygren and Larsson, 2014 ; Williamson et al, 2016 ; Nishi et al, 2017 ; Petersen and Baird, 2021 ), however mechanistic understanding using the whole signature is lacking. Conversely, the candidates generated via the interactomic signature pipeline (left, blue text) included telmisartan, nabumetone, fenofibrate, and mefenamic acid ( Ozeki et al, 2013 ; Mielczarek-Puta et al, 2020 ; Lee et al, 2014 ; Roy et al, 2001b ; a , 2005 ; Kong et al, 2021 ; Seyyedi et al, 2022 ; Hosseinimehr et al, 2019 ), which may be exerting their therapeutic effects via impacting multiple pathways implicated in colon cancer simultaneously ( Myung and Kim, 2008 ; Bahrami et al, 2018 ; Luo et al, 2019 ; Ungaro et al, 2020 ). Similarly, the top candidates for migraine disorders generated by the proteomic signature pipeline (right, red text) included methylergometrine and betaxolol ( Tfelt-Hansen et al, 1987 ; Koehler and Tfelt-Hansen, 2008 ), both of which can be seen as trivial due to other members of their respective drug classes already being commonly used treatments for migraines.…”
Section: Resultsmentioning
confidence: 99%